Penerapan Media Digital Wordwall Untuk Meningkatkan Minat Belajar Anak Dalam Mata Pelajaran Sejarah Kebudayaan Islam (SKI) di TPA Al-Amanah - Risma Ayu Ningtyas; Heny Narendrany Hidayati (EDU-RILIGIA: Jurnal Ilmu Pendidikan Islam dan Keagamaan, 2025)
Many students have not followed the Islamic Cultural History (SKI) learning optimally. This is due to their negative views on history subjects that only review the past, are boring and contain repetitive stories. Therefore, interactive digital media are needed that can attract students' attention and can form students' enthusiasm in the SKI learning process. One of the digital media used is wordwall. This article is compiled based on the author's experience as a teacher at TPA Al-Amanah who found that the lecture method was less effective in delivering SKI material. This study uses a qualitative method with a descriptive approach. Data collection techniques can be done through interviews, class observations and documentation. The results of the observation showed that there was an increase in student participation and interest in SKI learning at TPA AL-Amanah after using digital wordwall media. Students are more active, ask questions and show interest in the material because the nature of the wordwall itself is interactive and encourages fun learning.